2018
DOI: 10.1007/s11665-018-3340-8
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Graphene-Coated SiC Single Crystal and Liquid Copper

Abstract: The wettability of graphene-coated SiC single crystal (C Gn /SiC sc ) by liquid Cu (99.99%) was investigated by a sessile drop method in vacuum conditions at temperature of 1100°C. The graphene layer was produced via a chemical vapor deposition routine using 4H-SiC single crystal cut out from 6¢¢ wafer. A dispensed drop technique combined with a non-contact heating of a couple of materials was applied. The Cu drop was squeezed from a graphite capillary and deposited on the substrate directly in a vacuum chambe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…The results of structural analyses suggested that the presence of discontinuities in the graphene layer provoked by thermo-mechanical stresses occurred at high temperature, inhibit, but does not completely prevent, the chemical interaction between the liquid droplet of Cu and SiC sc . This effect was more pronounced for the Cu drops which were deposited on the C Gn /SiC sc substrate, structurally and chemically changed by previous contact with liquid Cu [5]. The behavior of the Cu drop in few attempts to detach it from the graphenecoated SiC substrate by rising up a graphite capillary showed a strong adhesion of the liquid Cu to the SiC.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The results of structural analyses suggested that the presence of discontinuities in the graphene layer provoked by thermo-mechanical stresses occurred at high temperature, inhibit, but does not completely prevent, the chemical interaction between the liquid droplet of Cu and SiC sc . This effect was more pronounced for the Cu drops which were deposited on the C Gn /SiC sc substrate, structurally and chemically changed by previous contact with liquid Cu [5]. The behavior of the Cu drop in few attempts to detach it from the graphenecoated SiC substrate by rising up a graphite capillary showed a strong adhesion of the liquid Cu to the SiC.…”
Section: Introductionmentioning
confidence: 95%
“…Specifically, examinations at the Sn/C Gn /Cu interface microstructure clearly put in evidence diffusion phenomena of Sn atoms allowed by discontinuities in the graphene layer, mainly produced by thermos-mechanical stresses at high temperature (stresses). The second attempt to experimentally investigate the "wetting transparency of graphene" was reported by Homa et al [5] for the Cu/C Gn /SiC sc (SiC singlecrystal) system. In particular, the behavior of a liquid Cu drop just dispensed on the surface of a monocrystalline SiC substrate coated by graphene (C Gn /SiC sc ), was similar on C Gn /SiC sc and SiC sc substrates: several attempts to detach the drop of Cu from the C Gn /SiC sc and SiCs substrates by raising the graphite capillary showed strong adhesion of the droplet to the substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3], their contact angle with the graphene layer is related to their interfacial free energy. Common plasmonic noble metals such as Au, Ag, and Cu present values of the contact angle with graphene of 113˚ [22], 114˚ [23], and 122˚ [24], respectively. It is also worth mentioning that while for Ag the contact angle remains stable in time [23], for copper the contact angle progressively reduces to a value of 60˚ in 30 min [24].…”
Section: Effect Of Nanoparticle Shape: Contact Angle Between Ga Nps Amentioning
confidence: 99%
“…Common plasmonic noble metals such as Au, Ag, and Cu present values of the contact angle with graphene of 113˚ [22], 114˚ [23], and 122˚ [24], respectively. It is also worth mentioning that while for Ag the contact angle remains stable in time [23], for copper the contact angle progressively reduces to a value of 60˚ in 30 min [24]. In the case of Ga, the contact angle with smooth graphene layers, like the ones in our experiments, is close to a hemispherical NP shape, ∼80˚.…”
Section: Effect Of Nanoparticle Shape: Contact Angle Between Ga Nps Amentioning
confidence: 99%